2008
DOI: 10.1002/bmc.1043
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive method for determination of salvianolic acid A in rat plasma using liquid chromatography/tandem mass spectrometry

Abstract: Salvianolic acid A (SAA), a major effective constituent of Salvia miltiorrhizas, is widely used in traditional Chinese medicine. A sensitive rapid analytical method was established and validated for SAA in rat plasma, which was further applied to assess the pharmacokinetics of SAA in rats receiving a single oral dose of SAA. The method used liquid chromatography tandem mass spectrometry in multiple reaction monitoring mode with chloramphenicol as the internal standard. A simple liquid-liquid extraction based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…Currently, there are only two reports regarding the pharmacokinetics of Sal A after oral administration in pure form; one in Sprague-Dawley rats (Pei et al. 2008 ) and the other in Beagle dogs (Sun et al. 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are only two reports regarding the pharmacokinetics of Sal A after oral administration in pure form; one in Sprague-Dawley rats (Pei et al. 2008 ) and the other in Beagle dogs (Sun et al. 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…By intravenous injection, 100 mg/kg Sal B reaches the maximal plasma concentration ( C max ) around 910 μg/ml, and the half life ( t 1/2 ) of Sal B is around 105 minutes [7]. For oral administration, the C max of 500 mg/kg Sal B is 1.5 μg/ml while 100 mg/kg Sal A is only 308 ng/ml; the t 1/2 is around 248 minutes for Sal B and 3.29 hours for Sal A [7,9]. The oral bioavailability of Sal B in a conscious rat is calculated to be 2.3% [7], which is higher than rats under general anesthesia reported by Zhang et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, it provided the least protection when fed to a whole organism and this could be due to its incomplete cellular absorption compared to SalB. This difference in absorption was previously demonstrated in rats whereby oral administration of SalA showed a significantly lower plasma concentration of only 308 ng/ml compared to SalB which reached 1.5 μg/ml (Y. T. Wu et al, 2006, Pei et al, 2008. The UPLC findings from this study further supported this claim with the concentration of SalB found in the brains of DWE-fed flies being three times more than that of SalA.…”
Section: Discussionmentioning
confidence: 91%
“…It also raised the likelihood that SalA and SalB were utilized by neurons in live organisms. However, there were undetectable levels of SalA and SalB in the heads, bodies and faeces which could be due to their short half-life (Pei et al, 2008, Y. T. Wu et al, 2006.…”
Section: Discussionmentioning
confidence: 97%